2021
DOI: 10.1097/bot.0000000000001857
|View full text |Cite
|
Sign up to set email alerts
|

Do Fully Threaded Transiliac–Transsacral Screws Improve Mechanical Stability of Vertically Unstable Pelvic Fractures? A Cadaveric Biomechanical Analysis

Abstract: Objective: To determine whether fully threaded transiliac–transsacral (TI-TS) fixation is biomechanically superior to partially threaded TI-TS fixation of vertically unstable transforaminal sacral fractures. Methods: Vertically unstable zone 2 sacral fractures were created in 20 human cadaveric pelves with a unilateral osteotomy and resection of 1 cm of bone through the foramen of the sacrum to represent comminution. Ten specimens received either 2 7.3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
11
0
2
Order By: Relevance
“…Os resultados indicam que, nesta análise biomecânica cadavérica com fixação instável, o deslocamento e a taxa de falha foram maiores nos espécimes de rosca parcial, enquanto espécimes de rosca total demonstraram maior força média até a falha. 23 Em um bloco de osso sintético com carga de cisalhamento, a carga de escoamento e o deslocamento de parafusos com rosca total foram 64% e 67% maiores do que os valores observados com parafusos de rosca parcial, respectivamente. 2 Em nosso estudo, assim como em pesquisas anteriores, os parâmetros observados, como por exemplo a força de compressão, foram muito variáveis (desvio-padrão até 9% da média em nosso estudo e de até 12% segundo outros autores); 19 embora tenhamos excluído os casos extremos de compressão interfragmentar da análise estatística, deve-se ressaltar a existência de valores aberrantes (►Fig.…”
Section: Discussionunclassified
“…Os resultados indicam que, nesta análise biomecânica cadavérica com fixação instável, o deslocamento e a taxa de falha foram maiores nos espécimes de rosca parcial, enquanto espécimes de rosca total demonstraram maior força média até a falha. 23 Em um bloco de osso sintético com carga de cisalhamento, a carga de escoamento e o deslocamento de parafusos com rosca total foram 64% e 67% maiores do que os valores observados com parafusos de rosca parcial, respectivamente. 2 Em nosso estudo, assim como em pesquisas anteriores, os parâmetros observados, como por exemplo a força de compressão, foram muito variáveis (desvio-padrão até 9% da média em nosso estudo e de até 12% segundo outros autores); 19 embora tenhamos excluído os casos extremos de compressão interfragmentar da análise estatística, deve-se ressaltar a existência de valores aberrantes (►Fig.…”
Section: Discussionunclassified
“…In our study, the distribution of the two transsacral screws in the TTS group was slightly different from that presented by Min et al, however, the results of this study suggested that TTS was more stable than TO for Denis II sacral fractures, which was consistent with the data presented by Min et al It is postulated that the stability in TTS comes from the biplanar stability of two screws and the additional cortical purchase in the contralateral ilium [ 16 ]. Shannon et al [ 15 ] further confirmed that the stability of full-threaded screws in TTS is better than the stability of half-threaded screws. It is, therefore, reasonable to conclude that the above three factors are the source of stability of TTS in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Transsacral screw fixation has been considered as an alternative to sacroiliac screw fixation, and has been effectively used in remedying the failure of sacroiliac screw fixation [ 14 , 15 ]. Biomechanical studies have shown that two transsacral screws (TTS) provide higher stability than sacroiliac screws and TO [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an injury to the posterior pelvic ring may extremely destabilize the whole pelvic ring and necessitate surgical intervention. The goals of the surgical intervention in such cases include anatomical reduction and subsequent maintenance of the acquired reduction to minimize complications, such as gait disturbance, chronic low‐back pain, neurological dysfunction, and malunion or nonunion 4,5 . A key aspect of the repair of a posterior pelvic ring injury is to confer the pelvic ring with enough stability to counterbalance the translational and rotational forces in the vertical and horizontal directions, respectively 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The goals of the surgical intervention in such cases include anatomical reduction and subsequent maintenance of the acquired reduction to minimize complications, such as gait disturbance, chronic low-back pain, neurological dysfunction, and malunion or nonunion. 4,5 A key aspect of the repair of a posterior pelvic ring injury is to confer the pelvic ring with enough stability to counterbalance the translational and rotational forces in the vertical and horizontal directions, respectively. 6 In addition, to improve the post-surgery life quality of the patient, the sacral implants used should have minimal adverse effects on the patient.…”
Section: Introductionmentioning
confidence: 99%